Anti-ultraviolet composite sheet and preparation method thereof and composite hose

Through specific raw material components and multi-layer structure design, the UV resistance and barrier properties of composite sheets are improved, the problem of prone to aging and yellowing in the existing technology is solved, and the stable and efficient UV resistance effect is achieved, and the high standard requirements for daily chemical packaging is met.

CN118700662BActive Publication Date: 2025-04-04REGO PACKING GZ IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410945556.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2025-04-04
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

The composite sheets of existing transparent hoses are prone to aging and yellowing, and their UV resistance is unstable, affecting the aesthetics of packaging and product quality.

Method used

Specific raw material components and ratios are adopted, including low-density polyethylene, linear low-density polyethylene, nano-concave-convex rod soil, sodium hydroxymethylcellulose, tributyl citrate and vinyl trimethoxysilane. The multi-layer structure design and alumina-plated PET film are used as a barrier layer to improve UV resistance and barrier properties.

Benefits of technology

It realizes the long-term stable UV resistance of composite sheets, avoids aging and yellowing, and meets the high standards for packaging materials for daily chemicals such as cosmetics and toothpaste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004945517110000081
    Figure BDA0004945517110000081
  • Figure BDA0004945517110000091
    Figure BDA0004945517110000091
  • Figure HDA0004945517120000011
    Figure HDA0004945517120000011
Patent Text Reader

Abstract

The present invention relates to the technical field of packaging materials, and specifically discloses an anti-ultraviolet composite sheet, a preparation method thereof, and a composite hose. An anti-ultraviolet composite sheet, from the inside to the outside, is sequentially an inner layer, a dry composite adhesive layer, a barrier layer, an extruded composite adhesive layer, and an anti-ultraviolet outer layer. The raw materials for preparing the anti-ultraviolet outer layer include 70 to 80 parts of low-density polyethylene, 20 to 30 parts of linear low-density polyethylene, 6 to 8 parts of nano-attapulgite, 1 to 2 parts of sodium hydroxymethyl cellulose, 2 to 3 parts of tributyl citrate, and 0.8 to 1.2 parts of vinyl trimethoxy silane. The anti-ultraviolet composite sheet prepared in the present application not only realizes effective shielding of ultraviolet rays, but also improves the aging resistance of the outer layer, ensuring that the stable anti-ultraviolet performance can be maintained during long-term use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, and in particular to an anti-ultraviolet composite sheet and a preparation method thereof, and a composite hose. Background Art

[0002] The demand for daily chemical packaging is growing, especially in the field of cosmetics and toothpaste packaging, and the requirements for packaging materials are becoming increasingly stringent. Because transparent hoses can perfectly show the color and texture of the product and attract consumers' attention, they are widely used in cosmetics and toothpaste. In order to improve the barrier performance of transparent hoses, most of the common transparent hoses on the market are made of composite sheets. Composite sheets are usually composed of a multi-layer structure, and the outer layer is often made of polyethylene. However, the ultraviolet transmittance of polyethylene is high, which makes the prepared composite sheets easy to age and turn yellow, which damages the appearance of the product and may even affect the quality of the product in the package.

[0003] In actual production, manufacturers often add UV absorbers, antioxidants and other ingredients to polyethylene to improve its UV resistance. Although this practice can indeed enhance the UV resistance of polyethylene to a certain extent, over time, these ingredients will gradually migrate and diffuse from polyethylene, gradually weakening the UV resistance of polyethylene, and eventually inevitably leading to the aging of polyethylene. These ingredients may even migrate to the products in the package, causing adverse effects on the products.

[0004] Therefore, how to improve the anti-ultraviolet performance of composite sheets and ensure their stable and long-lasting performance has become an urgent problem that needs to be solved. Summary of the invention

[0005] In order to improve the anti-ultraviolet performance of the composite sheet, the present application provides an anti-ultraviolet composite sheet and its preparation method and a composite hose. The present application realizes the effective shielding of ultraviolet rays by the anti-ultraviolet outer layer by selecting specific raw material components and proportions, while ensuring that the composite sheet can still maintain stable anti-ultraviolet performance during long-term use. The present application further combines the layer structure design of the inner layer and the barrier layer, especially selecting an aluminum oxide-coated PET film as the barrier layer, which significantly improves the barrier performance of the composite sheet, thereby meeting the high standard requirements for packaging materials for daily chemical products such as cosmetics and toothpaste.

[0006] In the first aspect, the present application provides an anti-ultraviolet composite sheet adopting the following technical solution:

[0007] The invention discloses an anti-ultraviolet composite sheet, comprising an anti-ultraviolet outer layer, wherein the raw materials for preparing the anti-ultraviolet outer layer comprise the following components in parts by weight: 70 to 80 parts of low-density polyethylene, 20 to 30 parts of linear low-density polyethylene, 6 to 8 parts of nano-attapulgite, 1 to 2 parts of sodium hydroxymethyl cellulose, 2 to 3 parts of tributyl citrate, and 0.8 to 1.2 parts of vinyltrimethoxysilane.

[0008] In the above technical scheme, low-density polyethylene and linear low-density polyethylene are used as the main raw materials of the anti-ultraviolet outer layer. Low-density polyethylene has good softness, extensibility, transparency, cold resistance and processability, which can give the anti-ultraviolet composite sheet good flexibility and processing performance. The addition of linear low-density polyethylene can improve the strength and heat resistance of the composite sheet and further enhance its physical properties. Nano-attapulgite has good ultraviolet light absorption and scattering properties, which can enhance the anti-ultraviolet effect of the anti-ultraviolet outer layer and prevent the composite sheet from aging and yellowing. Vinyltrimethoxysilane, as a coupling agent, can effectively improve the compatibility between inorganic nanomaterials and organic polymer materials in the anti-ultraviolet outer layer and improve the overall performance of the composite sheet. Sodium hydroxymethylcellulose and tributyl citrate, as stabilizers and plasticizers, can effectively enhance the antioxidant properties and flexibility of the anti-ultraviolet outer layer. At the same time, the present applicant discovered in the study that, under the synergistic effect of sodium hydroxymethyl cellulose, tributyl citrate and vinyl trimethoxy silane, nano-attapulgite can be more evenly and stably dispersed in the anti-UV outer layer and is not easily precipitated from the anti-UV outer layer, thereby being able to effectively exert the anti-UV effect for a long time while ensuring that the mechanical properties and processing properties of the anti-UV outer layer are not affected.

[0009] Preferably, the particle size of the nano-attapulgite ranges from 20 to 100 nm.

[0010] In the above technical scheme, the present application avoids the problem of insufficient transparency of the anti-ultraviolet outer layer due to excessive particle size by limiting the particle size range of nano-attapulgite, reduces the scattering loss of visible light of the material, and makes the material more transparent. At the same time, within this particle size range, the nano-attapulgite can be more evenly dispersed in the anti-ultraviolet outer layer, further avoiding particle aggregation, which is conducive to maintaining the transparency and aesthetics of the anti-ultraviolet outer layer. In addition, the nano-attapulgite within this particle size range is also easier to mix evenly with other raw materials, further improving the performance stability of the anti-ultraviolet outer layer. By optimizing the particle size of the nanomaterial, the present application ensures the transparency and aesthetics of the composite sheet while improving the anti-ultraviolet performance, meeting the high standards for packaging materials for daily chemical products such as cosmetics and toothpaste.

[0011] Preferably, the anti-ultraviolet composite sheet comprises, from inside to outside, an inner layer, a dry-bonded adhesive layer, a barrier layer, an extruded adhesive layer and an anti-ultraviolet outer layer; the inner layer is a polyethylene film; and the barrier layer is a PET film coated with aluminum oxide.

[0012] In the above technical scheme, the present application further improves the performance of the composite sheet by further defining the inner layer and barrier layer of the anti-ultraviolet composite sheet. The inner layer adopts a polyethylene film, which has good flexibility, transparency and processing performance, and can ensure the softness and easy processing of the composite sheet. The barrier layer adopts a PET film coated with a single layer of aluminum oxide. The addition of aluminum oxide gives the PET film excellent barrier properties, which can effectively prevent the penetration of substances such as gas and moisture, thereby protecting the products in the package from the influence of the external environment. At the same time, the PET film coated with a single layer of aluminum oxide also has excellent heat resistance and weather resistance, and can maintain stable performance in various harsh environments. By adopting this multi-layer structural design, the present application not only improves the anti-ultraviolet performance of the composite sheet, but also enhances its barrier performance, meeting the multiple demands of daily chemical products such as cosmetics and toothpaste for packaging materials.

[0013] Preferably, the barrier layer is a transparent barrier layer, and the coating thickness of the aluminum oxide is between 0.03 and 0.06 μm.

[0014] In the above technical solution, the present application further limits the transparency of the barrier layer and the thickness of the aluminum oxide coating, thereby maximizing the barrier performance without affecting the transparency of the composite sheet. The transparent barrier layer ensures the visual clarity and aesthetics of the composite sheet, while the thickness of the aluminum oxide coating is selected to prevent the increase in material costs and the increase in the difficulty of composite sheet processing due to excessively thick coating while maintaining high barrier properties. Within this thickness range, the PET film coated with a single layer of aluminum oxide can effectively block the penetration of substances such as gas and moisture without affecting the transparency and appearance of the composite sheet.

[0015] Preferably, the raw materials for preparing the inner layer include the following components in parts by weight: 70 to 80 parts of low-density polyethylene, 20 to 30 parts of linear low-density polyethylene and 5 to 10 parts of metallocene polyethylene.

[0016] In the above technical solution, metallocene polyethylene is a polyethylene material with excellent physical properties and processing properties. Its unique molecular structure gives it the characteristics of high transparency, high toughness, high strength and good thermal stability. Combining it with low-density polyethylene and linear low-density polyethylene can significantly improve the flexibility, transparency and heat resistance of the inner layer, improve the processing performance of the inner layer, ensure that the composite sheet has good performance, and meet the high standard requirements of daily chemical products such as cosmetics and toothpaste for packaging materials.

[0017] Preferably, the inner layer has a thickness of 50 to 110 μm, the dry composite adhesive layer has a thickness of 2 to 5 μm, the barrier layer has a thickness of 12 to 20 μm, the extruded composite adhesive layer has a thickness of 2 to 5 μm, and the UV resistant outer layer has a thickness of 50 to 110 μm.

[0018] In the above technical solution, the present application further optimizes the thickness of each layer to ensure that the composite sheet has good cost-effectiveness while maintaining excellent performance.

[0019] In a second aspect, the present application provides a method for preparing an anti-ultraviolet composite sheet using the following technical solution:

[0020] A method for preparing an anti-ultraviolet composite sheet comprises the following steps:

[0021] Step 1-1, production of the inner layer: taking the raw materials of the inner layer formula and mixing them evenly, melting them and then performing a film blowing process to obtain the inner layer;

[0022] Step 1-2, production of the UV-resistant outer layer: taking the raw materials of the UV-resistant outer layer formula and mixing them evenly, melting them, and then performing a film blowing process to obtain the UV-resistant outer layer;

[0023] Step 2: The side of the barrier layer coated with aluminum oxide film is bonded to the inner layer through a dry lamination process to form a dry lamination bonding layer; the side of the barrier layer not coated with aluminum oxide film is bonded to the anti-ultraviolet outer layer through an extrusion lamination process to form an extrusion lamination bonding layer, and finally an anti-ultraviolet composite sheet is obtained.

[0024] In the above technical scheme, the present application uses a specific formula and process to make the composite sheet have excellent UV resistance, barrier performance and processing performance. In the preparation process of the present application, the inner layer and the UV-resistant outer layer are first prepared separately, and then a complete UV-resistant composite sheet is formed through dry lamination and extrusion lamination processes. The preparation method is simple and easy to implement, and can efficiently prepare UV-resistant composite sheets with excellent performance, meeting the demand for packaging materials for daily chemical products such as cosmetics and toothpaste.

[0025] Preferably, the melting temperature in step 1-1 is 150-200°C;

[0026] The melting temperature in step 1-2 is 150-200°C.

[0027] In the above technical solution, the present application ensures the performance matching between the layers of the composite sheet and the optimization of the overall performance by further limiting the melting temperature of the inner layer and the UV-resistant outer layer.

[0028] In a third aspect, the present application provides a composite hose using the following technical solution:

[0029] A composite hose is prepared using the anti-ultraviolet composite sheet as described in the first aspect.

[0030] In the above technical solution, the present application adopts the above anti-ultraviolet composite sheet to prepare the composite hose, so that the composite hose has excellent anti-ultraviolet performance, barrier performance and aesthetics, and can meet the high standard requirements of daily chemical products such as cosmetics and toothpaste for packaging materials. At the same time, since the composite sheet has good processing performance, it can be easily prepared into composite hoses of various shapes and sizes to meet the packaging needs of different products. In addition, the composite hose also has excellent flexibility and durability, which can protect the product from the influence of the external environment and extend the shelf life of the product.

[0031] In summary, the present application includes at least one of the following beneficial technical effects:

[0032] 1. The present application creatively uses nano-attapulgite as the main anti-UV ingredient, and further creatively adds sodium hydroxymethyl cellulose, tributyl citrate and vinyl trimethoxy silane to the anti-UV outer layer, thereby ensuring that the main anti-UV ingredients in the anti-UV outer layer are not easy to diffuse and migrate, ensuring that the anti-UV outer layer can effectively play an anti-UV role for a long time, and at the same time ensuring that the mechanical properties and processing properties of the anti-UV outer layer are not affected.

[0033] 2. The anti-ultraviolet composite sheet provided in the present application adopts a multi-layer structure design. By selecting a PET film coated with a single layer of aluminum oxide as a barrier layer, and by adding components such as metallocene polyethylene to the inner layer, and through a specific formula and process, the composite sheet has excellent anti-ultraviolet performance, barrier performance and processing performance, meeting the multiple demands of daily chemical products such as cosmetics and toothpaste for packaging materials.

[0034] 3. The present application ensures the barrier and UV resistance of the anti-UV composite material while avoiding the problem of decreased transparency of the anti-UV composite material by limiting the coating thickness range of aluminum oxide in the barrier layer and the particle size range of nano zinc oxide and nano attapulgite in the anti-UV outer layer, thereby ensuring that the composite sheet has high transparency. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the structure of the anti-ultraviolet composite sheet of the present application.

[0036] Explanation of reference numerals: 100: UV-resistant composite sheet; 1: UV-resistant outer layer; 2: extruded bonding layer; 3: barrier layer; 301: surface coating layer formed by aluminum oxide plating; 4: dry bonding layer; 5: inner layer. DETAILED DESCRIPTION

[0037] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0038] Preparation Example 1

[0039] The invention discloses an anti-ultraviolet outer layer, wherein the raw materials for preparing the anti-ultraviolet outer layer include 70kg of low-density polyethylene, 30kg of linear low-density polyethylene, 6kg of nano-attapulgite, 2kg of sodium hydroxymethylcellulose, 3kg of tributyl citrate and 0.8kg of vinyl trimethoxysilane.

[0040] Among them, low-density polyethylene (LDPE) comes from Dow Chemical of the United States, brand: 4203.

[0041] Among them, linear low-density polyethylene (LLDPE) comes from Braskem of Brazil, brand: PEFM31D.

[0042] Among them, nano-attapulgite was purchased from Jiangsu Jiuchuan Nanomaterial Technology Co., Ltd. with a particle size of 20 to 100 nm.

[0043] Among them, sodium hydroxymethyl cellulose was purchased from Langfang Pengcai Fine Chemicals Co., Ltd.

[0044] Among them, tributyl citrate was purchased from Boxuan Chemical (Shandong) Co., Ltd., CAS No.: 77-94-1.

[0045] Among them, vinyltrimethoxysilane was purchased from Foshan Guiteng New Material Technology Co., Ltd., model: 171.

[0046] The method for preparing the UV-resistant outer layer comprises the following steps:

[0047] Step (1)-a: mixing low-density polyethylene and linear low-density polyethylene and stirring them uniformly;

[0048] Step (1)-b: mixing nano-attapulgite, sodium hydroxymethyl cellulose, tributyl citrate and vinyl trimethoxysilane and stirring evenly;

[0049] Step (2): After the mixture of step 1-3-1a is melted at 160°C, the mixture of step 1-3-1b is added, mixed evenly at high speed, and the masterbatch is extruded. The masterbatch is subjected to a film blowing process to obtain an anti-ultraviolet outer layer with a thickness of 110 μm.

[0050] The film blowing process is as follows: the masterbatch is added into the extruder and melted at 160°C and then extruded into a cylindrical (tube) shape. Compressed air is introduced to inflate the cylinder into a bubble tube shape. At this time, the bubble tube is elongated in both the vertical and horizontal directions to obtain a bubble tube that is inflated 3 times. The bubble tube is then flattened to prevent the air in the bubble tube from leaking out to maintain the required constant blowing pressure. The flattened bubble tube becomes a flat-folded double-layer film, which is finally wound into a winding device to complete the film blowing.

[0051] Preparation Example 2

[0052] An anti-ultraviolet outer layer, which is different from Preparation Example 1 in that the preparation raw materials include 80kg low-density polyethylene, 20kg linear low-density polyethylene, 8kg nano-attapulgite, 1kg sodium hydroxymethyl cellulose, 2kg tributyl citrate, and 1.2kg vinyl trimethoxy silane.

[0053] The method for preparing the UV-resistant outer layer comprises the following steps:

[0054] Step (1)-a: mixing low-density polyethylene and linear low-density polyethylene and stirring them uniformly;

[0055] Step (1)-b: mixing nano-attapulgite, sodium hydroxymethyl cellulose, tributyl citrate and vinyl trimethoxysilane and stirring evenly;

[0056] Step (2): After the mixture of step 1-3-1a is melted at 200°C, the mixture of step 1-3-1b is added, mixed evenly at high speed, and the masterbatch is extruded. The masterbatch is subjected to a film blowing process to obtain an anti-ultraviolet outer layer with a thickness of 110 μm.

[0057] Preparation Example 3

[0058] An anti-ultraviolet outer layer, which is different from Preparation Example 1 in that the preparation raw materials include 75kg low-density polyethylene, 25kg linear low-density polyethylene, 7kg nano-attapulgite, 1.5kg sodium hydroxymethyl cellulose, 2.5kg tributyl citrate, and 1kg vinyl trimethoxysilane.

[0059] The method for preparing the UV-resistant outer layer comprises the following steps:

[0060] Step (1)-a: mixing low-density polyethylene and linear low-density polyethylene uniformly;

[0061] Step (1)-b: mixing nano-attapulgite, sodium hydroxymethyl cellulose, tributyl citrate and vinyl trimethoxysilane uniformly;

[0062] Step (2): After the mixture of step 1-3-1a is melted at 150°C, the mixture of step 1-3-1b is added, mixed evenly at high speed, and the masterbatch is extruded. The masterbatch is subjected to a film blowing process to obtain an anti-ultraviolet outer layer with a thickness of 110 μm.

[0063] Comparative Preparation Example 1

[0064] An anti-ultraviolet outer layer, which is different from Preparation Example 1 in that an equal amount of sodium hydroxymethyl cellulose in the preparation raw materials is replaced by calcium stearate.

[0065] Comparative Preparation Example 2

[0066] An anti-ultraviolet outer layer, which is different from Preparation Example 1 in that an equal amount of tributyl citrate in the preparation raw material is replaced by propylene glycol dicaprylate.

[0067] Comparative Preparation Example 3

[0068] An anti-ultraviolet outer layer, which is different from Preparation Example 1 in that the vinyl trimethoxy silane in the preparation raw material is replaced by n-octyl triethoxy silane in equal amounts.

[0069] Comparative Preparation Example 4

[0070] An anti-ultraviolet outer layer is different from Preparation Example 1 in that the nano-attapulgite in the preparation raw material is replaced by nano-zinc oxide in an equal amount, and the particle size of the nano-zinc oxide ranges from 20 to 100 nm.

[0071] Example 1

[0072] The invention discloses an anti-ultraviolet composite sheet, which comprises an inner layer, a dry composite adhesive layer, a barrier layer, an extruded composite adhesive layer and an anti-ultraviolet outer layer from the inside to the outside. A coating layer formed by aluminum oxide coating is arranged on one side of the barrier layer close to the inner layer.

[0073] The raw materials for preparing the inner layer include 80kg of low-density polyethylene, 20kg of linear low-density polyethylene and 5kg of metallocene polyethylene.

[0074] Among them, the metallocene polyethylene comes from Dow, brand: PE5401.

[0075] The preparation of the inner layer comprises the following steps:

[0076] Low-density polyethylene, linear low-density polyethylene and metallocene polyethylene are mixed, melted at 160°C, mixed evenly at high speed, and extruded into master batches. The master batches are subjected to a film blowing process to obtain an inner layer with a thickness of 110 μm.

[0077] Among them, the barrier layer was purchased from Huizhou Yibai Technology Co., Ltd., and the preparation raw materials included polyethylene terephthalate and alumina, model: PET-AlOx-020, and the thickness of the coating layer formed by alumina plating was 0.06 μm.

[0078] The thickness of the barrier layer is 20 μm.

[0079] Among them, the UV-resistant outer layer comes from Preparation Example 1.

[0080] The dry composite adhesive layer is a layer structure formed by dry composite glue that bonds the inner layer and the barrier layer together.

[0081] Among them, the manufacturer of dry glue is Bostik, brand: bostikH108, bostik LF518.

[0082] The dry lamination process is as follows: first apply dry lamination glue on the inner layer, dry it in a 60°C oven to dry out all the solvent in the dry lamination glue, melt the dry lamination glue again under heating, and then laminate the barrier layer to it, and then cool it to form a dry lamination adhesive layer.

[0083] The thickness of the dry composite adhesive layer is 2 μm.

[0084] The extruded bonding layer is a layer structure formed by extruded polyethylene that bonds the barrier layer and the UV-resistant outer layer together.

[0085] Among them, extruded polyethylene is a mixture of Dow PE722 and Dow PE712 in a mass ratio of 1:1.

[0086] The extrusion process is as follows: the extruded polyethylene is melted at 160°C in an extruder to form a melt coating, and then evenly coated on the surface of the anti-ultraviolet outer layer, and then the anti-ultraviolet outer layer and the barrier layer are pressed together by a cooling roller to form an extruded bonding layer.

[0087] Wherein, the thickness of the extruded bonding layer is 2 μm.

[0088] The method for preparing the UV-resistant composite sheet comprises the following steps:

[0089] Step 1: Prepare the inner layer and the UV-resistant outer layer separately.

[0090] Step 2: The inner layer, barrier layer and UV-resistant outer layer obtained in step 1 are bonded together in turn through a dry lamination process and an extrusion lamination process to obtain an UV-resistant composite sheet.

[0091] Example 2

[0092] An anti-ultraviolet composite sheet, which is different from Example 1 in that:

[0093] The raw materials for preparing the inner layer include 70 kg of low-density polyethylene, 30 kg of linear low-density polyethylene and 10 kg of metallocene polyethylene.

[0094] The preparation of the inner layer comprises the following steps:

[0095] Low-density polyethylene, linear low-density polyethylene and metallocene polyethylene are mixed, melted at 200°C, mixed evenly at high speed, and extruded into master batches. The master batches are subjected to a film blowing process to obtain an inner layer with a thickness of 110 μm.

[0096] Among them, the UV-resistant outer layer comes from Preparation Example 2.

[0097] Example 3

[0098] An anti-ultraviolet composite sheet, which is different from Example 1 in that:

[0099] The raw materials for preparing the inner layer include 75 kg of low-density polyethylene, 25 kg of linear low-density polyethylene and 8 kg of metallocene polyethylene.

[0100] The preparation of the inner layer comprises the following steps:

[0101] Low-density polyethylene, linear low-density polyethylene and metallocene polyethylene are mixed, melted at 150°C, mixed evenly at high speed, and extruded into master batches. The master batches are subjected to a film blowing process to obtain an inner layer with a thickness of 110 μm.

[0102] Among them, the UV-resistant outer layer comes from Preparation Example 3.

[0103] Performance Testing

[0104] Detection 1

[0105] Sample: UV-resistant outer layer of the preparation example and the comparative preparation example.

[0106] The ultraviolet transmittance of the samples was tested by an ultraviolet spectrophotometer, and the tensile strength of the samples was tested by GB / T 1040.3.

[0107] After the samples were photo-aged for 1000 hours, the tensile strength of the samples was tested again. The aging conditions were: Xenon lamp aging test box X65, xenon arc lamp, irradiation intensity 60W / m 2 , spraying cycle: 102 minutes drying, 18 minutes water spraying.

[0108] The above test results are shown in Table 1.

[0109] Table 1:

[0110]

[0111] Combining Preparation Examples 1-3, Comparative Preparation Examples 1-4 and Table 1, it is not difficult to see that the UV-resistant outer layer of Preparation Examples 1-3 has good UV resistance and light aging resistance.

[0112] Specifically combined with the analysis of Preparation Example 1 and Comparative Preparation Examples 1-3, the difference between Preparation Example 1 and Comparative Preparation Examples 1-3 is that Comparative Preparation Examples 1-3 replace sodium hydroxymethyl cellulose, tributyl citrate and vinyl trimethoxy silane respectively, and Preparation Example 1 shows good UV resistance and aging resistance. Therefore, the applicant believes that sodium hydroxymethyl cellulose, tributyl citrate and vinyl trimethoxy silane have a synergistic effect. Adding sodium hydroxymethyl cellulose, tributyl citrate and vinyl trimethoxy silane to the anti-ultraviolet outer layer at the same time can promote the uniform dispersion of nano-attapulgite, and at the same time can significantly improve the stability of the anti-ultraviolet outer layer, ensure that the anti-ultraviolet outer layer can effectively play an anti-ultraviolet role for a long time, and delay the aging of the anti-ultraviolet outer layer.

[0113] Specifically combined with the analysis of Preparation Example 1 and Comparative Preparation Example 4, the main difference between the two is that Comparative Preparation Example 4 uses nano zinc oxide instead of nano attapulgite. Preparation Example 1 shows good aging resistance. Therefore, the applicant believes that sodium hydroxymethyl cellulose, tributyl citrate, vinyl trimethoxy silane and nano attapulgite have a good matching effect, which can further promote the close combination of the raw materials inside the anti-ultraviolet outer layer, further improve the structural stability, and thus show better aging resistance.

[0114] Detection 2

[0115] Sample: Anti-ultraviolet composite sheet of Example

[0116] The ultraviolet transmittance of the samples was tested by an ultraviolet spectrophotometer, the visible light transmittance of the samples was tested by ASTM D1003, the oxygen transmittance of the samples was tested by GB / T 1038, and the tensile yield stress and fracture growth rate of the samples were tested by GB / T 1040.3.

[0117] The above test results are shown in Table 2.

[0118] Table 2:

[0119]

[0120] In combination with Examples 1-3 and Table 2, it can be seen that the anti-ultraviolet composite sheet prepared in the present application has good transparency, barrier properties, UV resistance and mechanical properties. It can be seen that the present application has a good balance of the various properties of the composite sheet, and has developed a composite sheet with high transmittance, high barrier and UV resistance and good flexibility, which can be widely used in the packaging fields of cosmetics, toothpaste, etc., and is particularly suitable for packaging products that need to be exposed to the outdoors for a long time.

[0121] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An anti-ultraviolet composite sheet, characterized in that: The anti-ultraviolet composite sheet comprises, from inside to outside, an inner layer, a dry bonding layer, a barrier layer, an extruded bonding layer and an anti-ultraviolet outer layer; the inner layer is a polyethylene film; the barrier layer is a PET film coated with aluminum oxide; The anti-ultraviolet composite sheet comprises an anti-ultraviolet outer layer, and the raw materials for preparing the anti-ultraviolet outer layer comprise the following components in parts by weight: 70-80 parts of low-density polyethylene, 20-30 parts of linear low-density polyethylene, 6-8 parts of nano-attapulgite, 1-2 parts of sodium hydroxymethylcellulose, 2-3 parts of tributyl citrate, and 0.8-1.2 parts of vinyl trimethoxysilane; The raw materials for preparing the inner layer include the following components in parts by weight: 70-80 parts of low-density polyethylene, 20-30 parts of linear low-density polyethylene and 5-10 parts of metallocene polyethylene.

2. The anti-ultraviolet composite sheet according to claim 1, characterized in that: The particle size of the nano-attapulgite ranges from 20 to 100 nm.

3. The anti-ultraviolet composite sheet according to claim 1, characterized in that: The thickness of the inner layer is 50-110 μm, the thickness of the dry composite adhesive layer is 2-5 μm, the thickness of the barrier layer is 12-20 μm, the thickness of the extruded composite adhesive layer is 2-5 μm, and the thickness of the anti-ultraviolet outer layer is 50-110 μm.

4. A method for preparing an anti-ultraviolet composite sheet according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1-1, production of the inner layer: taking the raw materials of the inner layer formula and mixing them evenly, melting them and then performing a film blowing process to obtain the inner layer; Step 1-2, production of the UV-resistant outer layer: taking the raw materials of the UV-resistant outer layer formula and mixing them evenly, melting them, and then performing a film blowing process to obtain the UV-resistant outer layer; Step 2: The side of the barrier layer coated with aluminum oxide film is bonded to the inner layer through a dry lamination process to form a dry lamination bonding layer; the side of the barrier layer not coated with aluminum oxide film is bonded to the anti-ultraviolet outer layer through an extrusion lamination process to form an extrusion lamination bonding layer, and finally an anti-ultraviolet composite sheet is obtained.

5. The method for preparing an anti-ultraviolet composite sheet according to claim 4, characterized in that: The melting temperature in step 1-1 is 150-200° C.; The melting temperature in step 1-2 is 150-200°C.

6. A composite hose, characterized in that: The composite sheet is made of the anti-ultraviolet composite sheet as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Antibacterial and anti-ultraviolet PET / PTT alloy and preparation method thereof

    CN104845265A

  • Composite film for medicine package

    CN106626638A

  • Antitarnish thin film

    CN109263163A